Chromaticity-tunable remote LuYAG: Ce phosphor-in-glass film on regular textured glass substrate for white light emitting diodes. Issue 1 (January 2021) - Zhao, Guoying; Xu, Lingzhi; Guo, Yanyan; Hou, Jingshan; Liu, Yufeng; Zhou, Yan; Li, Ji-Guang; Fang, Yongzheng
Abstract: All inorganic remote phosphor-in-glass film exhibits excellent properties in high power white light-emitting-diodes (WLEDs) thanks to their easy fabrication and thermal stability. Herein, fabrication of (Lu, Y)3 Al5 O12 : Ce 3+ (LuYAG: Ce)phosphors embedded in borosilicate glass film by the conventional solid state reaction and spin coating technology has been reported. The introduction of Y 3+ ions reduces the difference of relative growth rate along some directions in growth of LuYAG microparticles, yielding a finer grain with smooth edges. By adjusting the molar concentration of Y 3+ ions in LuAG phosphor, a series of tunable broadband emission from green to yellow region is observed and maintains excellent thermal stability. Meanwhile, the decay curves of samples with different Y 3+ are almost same. SEM images show that phosphor particles are homogenously distributed within the glass matrix and keep their original morphology, suggesting the phosphor-in-glass films were synthesized as expected. Finally, a simple WLEDs based on the films was constructed using the commercial blue chip. The correlated color temperature ranging from 4853K to 4627K and high color rendering index from 81.4–79.7 were obtained. Upon the different driving current, the chromaticity coordinates of as-fabricated film exhibit good light color stability. These results bring an inspiring insight to tune the luminescent performance for remote WLEDs.